Disinfectan from Sodium Hypochloride And Essential Oil Prevents Covid-19 - Irma Susanti; Virgianti Nur Faridah; Rully Yuliandhari (Jurnal MIDPRO, 2021)
One of the efforts to prevent the transmission of COVID-19 is by disinfection of places/surfaces of inanimate objects such as door handles, tables, chairs, electric switches, banisters, bathrooms and others. The material that can be used to disinfect the surface of inanimate objects is NaOCl. The use of high-effectiveness NaOCl for disinfecting at low cost and easy use. NaOCl product on the market are generally only pure solutions without the addition of other ingredients so that the resulting NaOCl product give a distinctive odor of NaOCl which is sharp and hard to lose, so in this study, the addition of essential oils from fresh ginger and lemongrass which have anti-bacterial effectiveness for scent NaOCl covered. This research is an experimental research conducted at the Laboratory of Pharmaceutical Technology, University of Muhammadiyah Lamongan. The working procedure in this study is to make extracts from fresh ginger and lemongrass with maceration method by making NaOCl disinfectant solution with liquid extract from fresh ginger and lemongrass were then observed every month for 3 months in the study in the form of testing on alcohol levels and organoleptic of observations on color, odor and sediment. The results of this study showed that the disinfectant solution based on NaOCl with the addition of essential oils contained in the liquid extract of fresh ginger and lemongrass made by maceration method can change the scent of the product. The results of this formulation can be used as an alternative to disinfectants on the market.